PENGARUH PRAKTISI MENGAJAR TERHADAP CAPAIAN PEMBELAJARAN PENGANTAR AKUNTANSI DAN INVESTASI PASAR MODAL - Reny Wardiningsih; Lalu Andika Noviawan; Resty Yusnirmala Dewi; Khaerul Umam; Baiq Melyda Hasmi Aulia (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
This study focuses on analyzing the effect of the Practitioner Teaching Program on students’ learning outcomes in the courses of Introduction to Accounting and Capital Market Investment. The background of this research is based on the mismatch between graduates’ competencies and labor market demands, highlighting the need for more relevant and applicable learning approaches. This study employs a quantitative approach using a survey of 95 students selected through purposive sampling. Data were collected Likert-scale questionnaires and analyzed using simple linear regression with the assistance of SPSS software. The results indicate that practitioner involvement has a positive and significant effect on learning outcomes, with a significance value of 0.000 (<0.05) and a coefficient of determination (R²) of 0.778. Descriptively, the majority of students responded positively in terms of ease of understanding the material, learning interactivity, and relevance of the content to real-world practice. These findings suggest that practitioner involvement enhances the quality of learning, both cognitively and in terms of practical skills. The implications of this study emphasize the urgency of developing collaborative learning strategies between academics and practitioners in higher education.